Analysis of the Drag Flick Technique in the Indoor Hockey Game in the 2020 PON Papua Regional Youth Athletes in 2020 - Sri Rahayu; Daulay, Basyaruddin (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2021)
This study was to analyze the movement of the drag flick technique and to find out the correctness of the motion of the technique when dragging the flick on female athletes from the PON Papua 2020 plateaus. This study used a qualitative descriptive approach research design. By analyzing the motion of the drag flick technique for athletes who have participated in the National Training Program, which is used as a comparison and indoor hockey athletes from the Regional Plates of Prapon 2019 as athletes who are used as research samples using the Dartfish Teampro 5.5 software. This research was assisted by experts, namely one expert in the field of indoor hockey. The instrument used is Expert Judgment. The percentage of success that has been analyzed using Darfish software at the prefix position stage is very good (33%), Good (60%), Poor (6.6%), very poor (0%). the position of the foot crossover is very good (13%), Good (53.3%), Poor (33.3%), very poor (0%). the position of implementation is very good (22.2%), Good (50%), Poor (27.7%), very poor (0%). advanced motion positions are categorized as very good (0%), Good (34.7%), Less (65.2%), very poor (0%). The percentage of success based on expert judgment at the prefix position stage is Very Good (33%), Good (60%), Less (6.6%), Very Less (0%). foot crossover position is very good (13.3%), good (53.3%), less (33.3%), very poor (0%). the position of the implementation of the categories is Very Good (22%), Good (50%), Less (27.7%), Very Poor (0%). position ending in the category Very Good 34.7%), Good (65.2%), Less (0%), Very Less (0%). The results of the analysis of the overall movement of the dartfish software are at the level of correctness of the motion of the drag flick motion technique in the less category. The hockey sports expert's assessment shows that the overall motion at the correct level of motion of the drag flick technique is in the insufficient category so that there is still much to be improved.